2020
DOI: 10.1097/njh.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perceptions of the Palliative Care Needs of Neonates With Multiple Congenital Anomalies

Abstract: This study was conducted to determine neonatal intensive care unit (NICU) nurses' opinions about the palliative care needs of neonates with multiple congenital anomalies. The study sample consisted of the 20 nurses who agreed to participate in the study and worked in the NICU between November and December 2017. A one-to-one interview method was utilized using a semistructured interview form. Written consent was obtained from participants and reconfirmed verbally prior to data collection. In the study, most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Standards, care guidelines, and practice protocols for the palliative care of neonates in the intensive care setting have not yet been established in Turkey. Therefore, NICU staff need information about neonatal palliative care 4 . As neonatal palliative care is relatively new to Turkey, there have not been many studies examining neonatal nurses' attitudes toward palliative care and their views on the palliative care needs of newborns 4,5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Standards, care guidelines, and practice protocols for the palliative care of neonates in the intensive care setting have not yet been established in Turkey. Therefore, NICU staff need information about neonatal palliative care 4 . As neonatal palliative care is relatively new to Turkey, there have not been many studies examining neonatal nurses' attitudes toward palliative care and their views on the palliative care needs of newborns 4,5 …”
mentioning
confidence: 99%
“…Therefore, NICU staff need information about neonatal palliative care 4 . As neonatal palliative care is relatively new to Turkey, there have not been many studies examining neonatal nurses' attitudes toward palliative care and their views on the palliative care needs of newborns 4,5 …”
mentioning
confidence: 99%
“…Some nurses had limited training and experience in providing EOL care14–20 due to low patient numbers in their units,15–17and preferential allocation of ill patients to senior nurses 14–17. These nurses subsequently faced difficulty in shifting from a curative to a palliative care mindset, and felt overwhelmed when caring for dying neonates 14 16–21. HCP faced moral dilemmas due to unclear EOL care guidelines15 20 22 23 and differing management plans from various teams within the same NICU 17 18.…”
Section: Resultsmentioning
confidence: 99%
“…Differences of opinions in providing a newborn palliative care, with a dichotomy between comfort-focused care and disease-directed curative treatment, often led to intrateam conflict 10 12 18 21. Nurses felt they were helpless, especially when they disagreed with treatment decisions made by doctors,16 25 28 and felt compelled to obey doctors’ instructions 26.…”
Section: Resultsmentioning
confidence: 99%
“…16 Prior research has revealed differences between medical and nursing staffs' perceptions regarding palliative care facilitators and barriers within a NICU setting, recognizing not only prior training but also presence at the bedside as formative. 17 18 The predisposition of personalities toward certain professions, the acculturation of discipline-specific training, self-perceptions of professional roles in parental interactions, 19 and even the number of hours invested at the actual bedside necessarily informs and influences NICU profession-specific perspectives. 20 21 22 While certain disciplines in this study may have shared or emphasized a specific view during the interviews, the study team recognizes that this view does not necessarily predominate in the profession at large.…”
Section: Discussionmentioning
confidence: 99%